Adhesion Molecule CD146 and its Soluble Form Correlate Well with Carotid Atherosclerosis and Plaque Instability. (24th February 2014) - Qian, Yi‐Ning; Luo, Yong‐Ting; Duan, Hong‐Xia; Feng, Li‐Qun; Bi, Qi; Wang, Yong‐Jun; Yan, Xi‐Yun
Summary Aims Intraplaque neovascularization and foam cell infiltration contribute to the development of unstable plaque, leading to thromboembolism and stroke. Cell adhesion molecules (CAMs) have been reported to be involved in the progression of atherosclerosis and plaque vulnerability. The aim of this study was to assess the association of adhesion molecule CD146 with carotid plaque instability. Methods We collected forty atherosclerotic plaques from 40 patients undergoing carotid endarterectomy. The clinical information of each patient was obtained, and the plaque morphology and characteristics were examined by the ultrasound. The CD146 expressions of the plaques were graded by using semiquantitative scales. The serum level of soluble form of CD146 was detected by enzyme‐linked immunosorbent assay (ELISA). Results CD146 expression was mainly on the intraplaque blood vessels and infiltrated macrophages. The CD146 expression was strongly correlated with the matrix metalloproteinase‐9(MMP‐9)expressions (P < 0.001) in the plaques. Soluble CD146 (sCD146) was also elevated in patients with atherosclerotic plaques. There was significant correlation between the increased CD146 expression and sCD146 level (P = 0.0057). sCD146 correlated well with serum MMP‐9 (P < 0.0044), IL‐6 (P = 0.0044) and high sensitivity C‐reactive protein (hsCRP) (P = 0.005). Conclusions Adhesion molecules CD146 and its soluble form strongly correlated with the development of inflammation of atherosclerosis and plaque instability. CD146 may be a promising biomarker for monitoring the development and instability of atherosclerotic plaque in patients with carotid diseases.